A systematic review and meta-analysis of physical exercise non-adherence and its determinants among type 2 diabetic patients in Ethiopia. - Hailemicahel Kindie Abate; Abere Woretaw Azage; Alebachew Ferede Zegeye; Sintayehu Sime Tsega; Muluken Chanie Agimas; Habtamu Sewunet Mekonnen; Gashaw Adane Nega; Zarko Wako Beko; Chilot Kassa Mekonnen (PLoS ONE)
Introduction Physical exercise non-adherence is one of the leading risk behavioral factors for type two diabetic patients and one of the leading causes of mortality of patients worldwide. Therefore, the current study was conducted to determine the pooled prevalence and its determinants of non-adherence to physical exercise among type two diabetes adult patients in Ethiopia. Methods Studies were searched systematically using International databases from PubMed, Google Scholar, Cochrane Library, Embase, and CINAHL. The quality of articles that were searched was assessed using the New Castle Ottawa scale for a cross-sectional study design. Statistical analysis was performed using STATA version 14 and a meta-analysis was carried out using a random effect model method. Assessment of the certainty evidence's was done by applying the GRADE method. The Preferred Reporting Item for Systematic Review and Meta-analyses (PRISMA) guideline was followed for reporting results. The title and the protocol of this meta-analysis were registered at the online database PROSPERO registration number CRD42023430579. Result From the total 1711 records screened, 7 studies with 3437 participants who fulfilled the inclusion criteria were included in this systematic review. The estimated pooled prevalence of exercise non-adherence in Ethiopia was 50.59%. Being female (OR = 1.27, 95% CI (1.82, 1.97)), primary level education (OR = 1.19, 95% CI (1.01, 1.39)) and rural residency (OR = 4.87, 95% CI (2.80, 8.48)) were significantly associated with exercise non-adherence. Conclusion According to papers evaluated by the GRADE assessment the certainty of evidence's was poor. More than half of the diabetes patients had physical exercise non-adherence. Strategies such as emotional support, health education, and emphasis on rural diabetic patients can improve the problem of non-adherence.